Development of Lectora Inspire Application-Based E-Modules on The Topic of Coloid Systems - Sari, Sri Adelila; Yustika, Merry (PAEDAGOGIA, 2023)
The problem that often occurs during the learning process is that students feel bored and do not focus on the material taught by the teacher. Hence, students are not active during the discussion process, and these problems result in low student learning outcomes. In this case, the teacher seeks to arouse student interest and motivate students to be more enthusiastic about learning using the Lectora Inspire application-based learning media. This type of research was research and development (R&D) using the 4D model consisting of 4 stages: define, design, develop, and disseminate. The define stage was carried out by analyzing to obtain information in the field. The design was done by making an e-module design; the development stage is developing e-modules using Lectora Inspire and conducting assessments and trials. The final stage was dissemination, namely disseminating e-modules. After being validated, the research results showed that modules based on Lectora inspire applications in the colloid system course were declared feasible after being validated by material experts, media experts, teacher responses, and student responses. Assessment of material and media experts with an average percentage of 90.41% with the appropriate/valid category, the percentage of teacher responses was 84.76% with very high criteria, and the percentage of student responses was 83.54% with very high criteria. Based on the results of the n-gain score of 0.62 with a moderate category, the Lectora inspire-based e-module effectively improves learning outcomes. It can be concluded that the electronic module based on the inspirational Lectora application as an interactive learning medium effectively improves student learning at school.